Study of the deposition and resuspension phase of aerosol particles in a straight test pipe - Kumar, Manish; Joshi, Manish; Dwivedi, Anubhav Kumar; Kumar, Sidyant; Saud, T.; Khan, Arshad; Mishra, Gaurav; Saha, Nandan; Ganju, Sunil; Tripathi, S. N.; Sapra, B. K. (Frontiers in Nuclear Engineering, 2025)
The study of the transport and deposition characteristics of aerosol particles in test sections is a component of the probabilistic safety assessment of nuclear reactors under severe accident scenarios. The deposited particles may become resuspended under favorable conditions, thus affecting the source term estimates. The objective of the present study was to perform experiments on a straight test pipe section 4 m long under deposition and resuspension phases. Zinc oxide metal particles generated from a plasma torch aerosol generator (PTAG) were used as the test aerosols. Deposition phase experiments were performed at a total carrier gas flow rate of 180 Lmin-1, whereas the flow was increased to 1265 Lmin-1 for the resuspension phase. Thermophoresis as an effect of PTAG enthalpy-governed temperature gradients was seen to dominate the deposition phase. The effects of varying Reynold numbers in different volume sections were reflected in a higher resuspended-to-deposited-mass-ratio in the downstream direction. A profile of deposited and resuspended masses was interpreted for the resuspension time of 20 min. Experimentally obtained characteristics were also compared with numerical results from simulations performed with the SOPHAEROS module of the Accidental Source Term Evaluation Code (ASTEC). This study, performed at the National Aerosol Facility (NAF), Indian Institute of Technology, Kanpur, India, indicates the need of more research on aerosol resuspension effects as this impacts the estimation accuracy of the source term.